Phenological event detection by visual rhythm dissimilarity analysis - Santos, Lilian C. B. dos; Almeida, Jurandy; Santos, Jefersson A. dos; Guimaraes, Silvio Jamil F.; Araujo, Arnaldo De A.; Alberton, Bruna [UNESP]; Morellato, Leonor Patrícia Cerdeira [UNESP]; Torres, Ricardo da S.; IEEE (Ieee, 2014)
Plant phenology has been exploited as an important research venue for assessing the impact of climate changes. One common approach for monitoring vegetation relies on the use of digital cameras. The employment of imaging techniques for phenological observation allows the extraction and analysis of visual characteristics based on color and texture information with the objective of determining plant life cycle changes, such as the beginning of the leaf flushing or the senescence period. This paper presents a novel approach for detecting phenological changes by analyzing image temporal series. Our method is based on the use of visual rhythm analysis and the adoption of a dissimilarity measure to detect visual changes in the time line. Experiments were conducted on a three-year data set composed of 3,538 vegetation images and 21 samples of 6 different species of interest. Results demonstrate that the proposed change detection approach is able to effectively identify phenological events.